Degradation of refractory organics in concentrated leachate by the Fenton process: Central composite design for process optimization - Yazici Guvenc, Senem; Varank, Gamze (HIGHER EDUCATION PRESS, 2021)
The primary aim of this study is inert COD removal from leachate nanofiltration concentrate because of its high concentration of resistant organic pollutants. Within this framework, this study focuses on the treatability of leachate nanofiltration concentrate through Fenton oxidation and optimization of process parameters to reach the maximum pollutant removal by using response surface methodology (RSM). Initial pH, Fe2+ concentration, H2O2/Fe2+ molar ratio and oxidation time are selected as the independent variables, whereas total COD, color, inert COD and UV254 removal are selected as the responses. According to the ANOVA results, the R-2 values of all responses are found to be over 95%. Under the optimum conditions determined by the model (pH: 3.99, Fe2+: 150 mmol/L, H2O2/Fe2+: 3.27 and oxidation time: 84.8 min), the maximum COD removal efficiency is determined as 91.4% by the model. The color, inert COD and UV254 removal efficiencies are determined to be 99.9%, 97.2% and 99.5%, respectively, by the model, whereas the total COD, color, inert COD and UV254 removal efficiencies are found respectively to be 90%, 96.5%, 95.3% and 97.2%, experimentally under the optimum operating conditions. The Fenton process improves the biodegradability of the leachate NF concentrate, increasing the BOD5/COD ratio from the value of 0.04 to the value of 0.4. The operational cost of the process is calculated to be 0.238 (sic)/g CODremoved. The results indicate that the Fenton oxidation process is an efficient and economical technology in improvement of the biological degradability of leachate nanofiltration concentrate and in removal of resistant organic pollutants. (c) Higher Education Press 2020
Keywords: Concentrated leachate; Fenton oxidation; Central composite design; Biodegradability; Inert COD; ADVANCED OXIDATION PROCESSES; WASTE-WATER TREATMENT; LANDFILL LEACHATE; ELECTRO-FENTON; HETEROGENEOUS FENTON; UV-FENTON; REMOVAL; REACTOR; MATTER; ACID; Engineering; Environmental Sciences & Ecology